Efficacy of HLA-compatible Platelet Transfusion for Patients with Acute Myeloid Leukemia Refractory to Platelet Transfusion. (28th October 2020) - Tsai, T; Perez-Alvarez, I; Woo, J; Tran, M
Abstract: Introduction/Objective: Acute myeloid leukemia (AML) patients often require transfusion support during induction chemotherapy. Platelet transfusion refractoriness (PTR) may develop due to HLA alloimmunization. Management of immune-refractory patients with HLA-compatible platelet transfusions is labor intensive and associated with increased costs. The purpose of this study is to evaluate the efficacy of HLA-compatible platelet units in AML patients. Methods: Newly diagnosed AML patients undergoing induction chemotherapy in our institute between 2015 and 2018 were identified. Platelet counts and platelet transfusion data from initiation of chemotherapy until platelet recovery (> 20K/µL and increased consistently) were extracted. A 24-hour posttransfusion corrected count increment (CCI) was calculated to evaluate the efficacy of each platelet transfusion. PTR was declared if a patient had a 24-hour CCI < 4K following two consecutive transfusions. Student's t-test was used for statistical analysis. Results were presented as mean ± SE, * if p < 0.05. Results: We identified 39 patients with newly diagnosed AML. PTR developed in 22/39 (56%) patients during induction chemotherapy. The average CCI was higher among those without PTR compared to those with PTR (8, 408 ± 585 vs. 2, 923 ± 360*), and overall platelet transfusion burden (in number of units) was lower (7.29 ± 1.0 vs. 18.55 ± 1.71*). HLA antibodies were identified in 3/22 (14%) PTR patients, as 6/22 (27%) were tested. The average CCI during HLA matched transfusions for these 3 patients was higher than that with random units (2, 059 ± 149 vs. -126 ± 306*). Compared to HLA-negative PTR patients receiving random units, the average CCI for HLA-compatible transfusions was still lower, though not significantly (2, 059 ± 149 vs. 3, 099 ± 390, p = 0.33), while the number of HLA- compatible units transfused was significantly higher (31.0 ± 3.0 vs. 16.6 ± 1.45*). Conclusion: In a cohort of newly diagnosed AML patients undergoing induction chemotherapy whose PTR was associated with detectable HLA antibodies, transfusion support with HLA-matched products did not lead to reduced overall platelet transfusion rates and CCI remains in the refractory range. This suggests that use of HLA matched platelets among newly diagnosed AML patients with PTR, even in the setting of detectable HLA antibodies, does not appear to result in reduced overall product utilization.